HAMBATAN DAN SOLUSI DALAM PRAKTIK BANK GARANSI BAGI MASYARAKAT PENGGUNA (Tinjauan Sistem Syariah dan Konvensional) - Muttatoh Hirin (Lembaga penelitian dan pengabdian kepada masyrakat, 2014)
Bank Guarantee is applicable on Islamic Banking is a letter issued to ensure certainty (quality and timeliness) of a construction project or to guarantee performance (performance ) one of the parties in a transaction . The concept and implementation of a performance bond owned and has been applied by the Islamic Bank shall adhere to the National Fatwa Council of Indonesian Ulama Council Sharia governing kafalah . Basically the implementation of a bank guarantee in the conventional system and the Sharia system is almost the same . What distinguishes it is the opponent who handed over the management of customers' collateral to the bank . Viewed from the bottom loading Islamic Banking fees charged to its customers , then the basis of the calculated load is lighter than the burden given by the conventional banking to its customers , it can be seen from the types of costs to be incurred by the conventional banking customers , which consists of the cost of provision where average of 1% of the value of the bank guarantee , the administrative costs and the cost of stamp duty ,while charging for Islamic Banking is measured by the accumulation of cost components where results from the accumulation is not a percentage of the nominal value . Regarding kafalah there are some things that need to be refined as follows: first, Kafalah currently provided by Islamic banks in Indonesia based on the rules of conventional bank guarantee with absolute kafalah not the same, then the provision of services kafalah is regulated in a separate regulation. Second, kafalah in Islamic Banking services should be further improved. Again, it needs to be fixed is the promotion of the introduction of these services and the existence of effective and efficient services to the services to be widely known and disseminated to the public.